2009
DOI: 10.4103/0256-4947.51796
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of hepatitis C virus genotype-4 infection following orthotopic liver transplantation: Natural history and predictors of outcome

Abstract: BACKGROUND AND OBJECTIVES:There are few reports on hepatitis C virus genotype 4 (HCV-4) recurrences after orthotopic liver transplantation (OLT). Therefore, we undertook a study to determine the epidemiological, clinical and virological characteristics of patients with biopsy-proven recurrent HCV infection and analyzed the factors that influence recurrent disease severity. We also compared disease recurrence and outcomes between HCV-4 and other genotypes.PATIENTS AND METHODS:All patients who underwent OLT (loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…On the other hand, studies from the Middle East show a more favorable outcome of HCV-4 patients. In a study from Saudi Arabia on biopsy proven recurrence HCV post-OLT there were no significant differences between genotype 1 and 4 patients in terms of epidemiological, clinical, and histological factors as well as outcome (patients and graft survival) [127]. Among many epidemiologic, laboratory, virologic factors included in that analysis, the only factor predictive of an advanced histological score was the HCV RNA level at the time of biopsy.…”
Section: Liver Transplantationmentioning
confidence: 87%
“…On the other hand, studies from the Middle East show a more favorable outcome of HCV-4 patients. In a study from Saudi Arabia on biopsy proven recurrence HCV post-OLT there were no significant differences between genotype 1 and 4 patients in terms of epidemiological, clinical, and histological factors as well as outcome (patients and graft survival) [127]. Among many epidemiologic, laboratory, virologic factors included in that analysis, the only factor predictive of an advanced histological score was the HCV RNA level at the time of biopsy.…”
Section: Liver Transplantationmentioning
confidence: 87%
“…We have previously compared the recurrence and outcome between HCV genotype 4 and other genotypes following liver transplantation [18]. In that study, there was no significant difference in the 3-year survival, histological disease staging, and graft loss when comparing patients with genotype 4 to other genotypes.…”
Section: Discussionmentioning
confidence: 97%
“…They found that in the initial liver biopsy, which was performed after a mean time from transplantation of more than 2 years, there were only four patients who had fibrosis scores greater than stage 3. Two of these patients progressed to cirrhosis on subsequent biopsies [54]. Among many factors included in that analysis, the only factor predictive of an advanced histological score was the HCV RNA level at the time of biopsy.…”
Section: Natural History Of Hcv-g4 After Liver Transplantationmentioning
confidence: 99%